Fiscal Policies for Achieving Finland's Emission Neutrality Target - Parry, Ian.; Wingender, Philippe (Washington, D.C. : International Monetary Fund, 2021)
Finland has pledged to cut net greenhouse gas emissions to zero by 2035 and has sectoral targets for deploying electric vehicles, phasing out coal generation, and oil-based space heating. Fiscal policies at the national and sectoral level could play a critical role in achieving these objectives. Carbon dioxide emissions are already priced significantly in Finland but prices vary substantially across fuels and sectors. The paper discusses a reform to both scale up, and progressively harmonize, pricing while using revenues to address equity issues. It also discusses the potential use of revenue-neutral feebate schemes to strengthen mitigation incentives for the transportation, industry, building, forestry, and agricultural sectors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Climate; Energy; Informal Economy; Natural Disasters and Their Management; Underground Econom